ОСОБЕННОСТИ АНТИБАКТЕРИАЛЬНОЙ ТЕРАПИИ ХРОНИЧЕСКОГО БАКТЕРИАЛЬНОГО ПРОСТАТИТА НА ФОНЕ АТИПИЧНОЙ УРОИНФЕКЦИИ - Феоктистов , В.; АмантаеваM.; ВейсенбергT. (EurasianUnionScientists, 2021)
This study was made of 87 patients with a chronic bacterial prostatitis complicated by atypical uroinfection. The endocellular pathogens were identified among 38 patients on the background of chronic kidney disease in the acute phase and among 49 patients in the lag phase. There were identified 97 cultures in total. The associative microflora has been submitted by mainly two-componential association and was observed in 19 % cases. The 6 types of bacteria, by general number 127 of cultures, were allocated in microbiological research of a secret prostate before the beginning of treatment. In 17 monitorings there were associations of culture, in other cases as monocultures. Patients received in tablet form of roxithromycini in a daily dose of 300 mg, azithromycini in a daily dose of 1000 mg and josamycini in a daily dose 1500 mg during 10-14 day. The maximal clinical and bacteriological efficiency of treatment was marked in case of application josamycini.